2014
DOI: 10.1002/mop.28418
|View full text |Cite
|
Sign up to set email alerts
|

Design and characterization of a novel diamond resonator

Abstract: In this paper, the resonant frequency and quality factor of a novel coplanar waveguide (cpw) diamond shaped resonator was analysed using Advanced Design System (ADS-2009) finite element software. The diamond resonator was compared with the cpw radial stub resonator on gallium arsenide (GaAs); the work indicated that the diamond resonator had a smaller physical size and higher quality factor (Q) at milli-metric wave frequencies. Experimentally measured diamond cpw resonators fabricated on gallium arsenide (GaAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Recently, a new technique has been developed to calculate the resonant frequency of the unstructured resonators . In the present work, a similar approach is adopted to calculate the resonant frequency of the diamond‐shaped monopole antennas as a function of inner length at a fixed sectorial angle and is given in a polynomial form as f0= 3×106L15+5×104 L140.0337L13+1.0827L1217.29L1+115.89 the polynomial coefficients in Equation are specific adaptations to accommodate different sectorial angles. Figure shows the comparison of a resonant frequency between the simulated diamonds shaped monopole antenna and a simple monopole wire antenna.…”
Section: Simulation Results Of a Diamond‐shaped Monopole Antennasmentioning
confidence: 99%
“…Recently, a new technique has been developed to calculate the resonant frequency of the unstructured resonators . In the present work, a similar approach is adopted to calculate the resonant frequency of the diamond‐shaped monopole antennas as a function of inner length at a fixed sectorial angle and is given in a polynomial form as f0= 3×106L15+5×104 L140.0337L13+1.0827L1217.29L1+115.89 the polynomial coefficients in Equation are specific adaptations to accommodate different sectorial angles. Figure shows the comparison of a resonant frequency between the simulated diamonds shaped monopole antenna and a simple monopole wire antenna.…”
Section: Simulation Results Of a Diamond‐shaped Monopole Antennasmentioning
confidence: 99%
“…Whilst using the simulation tool it was found that the choice of mesh size was particularly important in order to obtain a realistic return loss of the dipole antenna especially at higher frequencies [6]. Initial simulation results show that the dipole antennas are resonant at 5.6 GHz with a bandwidth of ~ 1.2 GHz.…”
Section: Simulation Results Of Dipole Antennasmentioning
confidence: 99%
“…The polynomial equations are given by Eqs. and , respectively, . f0(Radicalstubresonator)=1060.1R42768R3+2713.1R21231.5R+253.7 f0(Diamondstubresonator)=3221L48368L3+7827L23180L+530.9 “ R ” represents the inner radius of the radial stub resonator and “ L ” represents the inner length of the diamond stub resonator.…”
Section: Design Fabrication and Simulation Of The Cpw Resonatorsmentioning
confidence: 99%
“…Microwave integrated resonators are widely used in microwave and milli‐metric components, which include filters , oscillators , and antennas . One form of the integrated resonator is the coplanar waveguide (cpw) radial resonator and more recently the diamond resonator which has been shown to occupy 55% less chip area than a comparable radial stub resonator . An important parameter of any resonator is its “quality factor” Q , which determines its frequency response .…”
Section: Introductionmentioning
confidence: 99%